2011
DOI: 10.1007/s11524-010-9542-5
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Populations—Sexual Risk Behaviors and HIV Prevalence in Clients and Partners of Female Sex Workers, Bangkok, Thailand 2007

Abstract: The aim of this study is to estimate HIV prevalence and assess sexual behaviors in a high-risk and difficult-to-reach population of clients of female sex workers (FSWs). A modified variation of respondent-driven sampling was conducted among FSWs in Bangkok, where FSWs recruited 3 FSW peers, 1 client, and 1 nonpaying partner. After informed consent was obtained, participants completed a questionnaire, were HIV-tested, and were asked to return for results. Analyses were weighted to control for the design of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Furthermore, respondents with early sexual debut were more likely to have paid someone for sexual activity. This is particularly worrisome because individuals who pay for sex are considered to be a bridging population for STIs/HIV, as their paid partners are often individuals at higher STIs/HIV risk [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, respondents with early sexual debut were more likely to have paid someone for sexual activity. This is particularly worrisome because individuals who pay for sex are considered to be a bridging population for STIs/HIV, as their paid partners are often individuals at higher STIs/HIV risk [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Findings from a study in Bangkok, Thailand reported that 20% (95% CI 12.1–31.2%) of male clients were infected with HIV, and similar prevalence was found among FSW with whom they had sex. Almost 25% of these male clients were married and more than 85% reported more than one sexual partner in the past month [11]. Findings from Yunnan, China, on the border with Vietnam, showed HIV prevalence among male clients to be 9.2% and to be most associated with injecting drug use and co-infection with herpes simplex virus type 2 (HSV-2) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Thailand and elsewhere suggest that clients of sexual workers may serve as a bridge for transmitting HIV from high-risk populations to the general population 11 12. Many male clients of HSWs in Pakistan are married or have girlfriends, and they may also have FSW contacts.…”
Section: Introductionmentioning
confidence: 99%